Individual variability and the H* ~ L + H* contrast in English - Riccardo Orrico; Stella Gryllia; Jiseung Kim; Amalia Arvaniti (Language and Cognition)
The H* ~ L + H* pitch accent contrast in English has been a matter of lengthy debate, with some arguing that L + H* is an emphatic version of H* and others that the accents are phonetically and pragmatically distinct. Empirical evidence is inconclusive, possibly because studies do not consider dialectal variation and individual variability. We focused on Standard Southern British English (SSBE), which has not been extensively investigated with respect to this contrast, and used Rapid Prosody Transcription (RPT) to examine differences in prominence based on accent form and function. L + H*s were rated more prominent than H*s but only when the former were used for contrast and the latter were not, indicating that participants had expectations about the form–function connection. However, they also differed substantially in which they considered primary (form or function). We replicated both the general findings and the patterns of individual variability with a second RPT study which also showed that the relative prioritization of form or function related to participant differences in empathy, musicality and autistic-like traits. In conclusion, the two accents are used to encode different pragmatics, though the form–function mapping is not clear-cut, suggesting a marginal contrast that not every SSBE speaker shares and attends to.